Revolutionizing Food Waste Reduction: Indonesia's Gen Z Entrepreneurs' Innovative Business Ideas (Journal of Namibian Studies : History Politics Culture, 2023)
The aim of the study was to describe Indonesia Gen Z's (people born in the late 1990s to the early 2010s) intention towards waste business management. This study was an extension of the previous research model by Huang et al. (2022), which examined the influencing factors of behavioral intention leading to sorting and recycling behaviors among youth. In order to provide empirical evidence from a developing country, the study used measurement instruments from Huang et al. (2022) and looked specifically at Indonesia, as the original research was conducted in developed countries (China and Finland). The research study was based on a qualitative approach, with active students from Indonesia International Institute for Life Sciences (i3L) as participants. The i3L has two main schools from life sciences and business school, which provided a good combination of students from a life sciences background and those studying business management, to create the Business Model Canvas (BMC) to reduce food waste.